UJI PENGARUH PUPUK ORGANIK CAIR DARAH SAPI DAN KCl TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis quineensis Jacq) DI PRE-NURSERY: TESTING THE INFLUENCE OF LIQUID ORGANIC FERTILIZER COW BLOOD AND KCl ON THE GROWTH OF PALM OIL (Elaeis quineensis Jacq) SEEDLINGS IN PRE-NURSERY - Mahdalena; Urlis Bauana (Universitas Widya Gama Mahakam, 2024)
The growth of oil palm plants is greatly influenced by the availability of nutrients in the soil. The availability of nutrients is determined by the physical, chemical and biological properties of the soil. Marginal soils such as Ultisol have very low levels of nutrient availability. This is caused by intensive weathering processes. Therefore, it is necessary to improve soil fertility. One effort that can be made to improve the fertility of Ultisol soil so that oil palms can grow well is by adding natural fertilizer. Natural fertilizer can come from the use of plant or animal remains. One of them is the use of cow blood waste, this waste has not been widely used as a source of natural fertilizer. One type of mineral soil that is widely used as a medium for growing seeds is ultisol soil. This happens because this type of soil is spread quite widely in Indonesia. The weakness of Ultisol soil as a growing medium is that this soil generally reacts very acidly. Therefore, to increase the growth of plant seeds, a good growing medium is needed for plants. To create a good growing medium, fertilizer is needed that contains alkaline reacting substances such as Potassium (K). One type of fertilizer that contains potassium is KCl fertilizer (Nugroho, 2000). The aim of the research is to determine the effect of liquid organic fertilizer from cow's blood and gamal leaves on the growth of oil palm seedlings. The research was carried out for 20 weeks (5 months) starting from February – June 2024. The research was carried out at the Agrotechnology Experimental Garden at Widya Gama Mahakam University, Samarinda. This research was organized in a Randomized Group Design (RAK) with Factorial analysis of 2 factors with 3 replications and obtained 48 polybags as follows: Cow Blood Liquid Organic Fertilizer consisting of 4 levels, namely: D0 (No Control Treatment), D1 (80 mL /L water), D2 (100 mL/L water) D3 (120 mL/L water). The second factor is KCl (K) fertilizer which consists of 3 levels, namely: K0 (0 g/tan), K1 (0.15 g/tan) and K2 (0.30 g/tan). Data were analyzed using analysis of variance based on the F test 5% and 1%. If it has a real effect, continue with the 5% BNT test. Keywords: Cow Blood, Elaeis, KCl, Liquid Organic Fertilizer,